ISOLATION AND IDENTIFICATION OF BACILLUS subtilis AND EVALUATION OF ANTAGONISM IN VITRO AGAINST PHYTOPATHOGENIC FUNGI (Nexo Revista Científica, 2018)
Plant pathogens microorganisms are an important threat to food production and their control through the use of antagonistic microorganisms is a world practice, which has led to research and search for new isolates that are effective in biological control. In this investigation the isolation and identification of bacterium from bioinsumos produced in Nicaragua was carried out and its antagonism against phytopathogenic fungi of agricultural interest was evaluated in vitro. Morphological characterization of 14 bacterial isolated and confirmation by sequencing of the 16S rDNA gene; later the antagonistic potential was evaluated by dual confrontation against the fungi identified as Fusarium equiseti, Fusarium sp. and Alternaria alternata. As a result, 6 inhibitory strains were found, with Bacillus subtilis strain F showing the best percentages of inhibition of the growth of phytopathogens evaluated in a range of 50-100%. Other interesting results were obtained by the identification of Bacillus megaterium and the use of Rhizobium sp, the latter inhibited between 50-90% the growth of fungi, which suggests to consider its application not only as a biostimulant, but also as a bioprotector when inhibiting of growth of certain phytopathogens.